Análisis del paisaje sonoro y su relación con la contaminación por ruido ambiental para la denominada zona norte de la ciudad de Medellín (2018)
This work proposes the development of the analysis of the soundscape for the north zone of Medellin, where five open public spaces were studied, such as: Ruta N, Jardín Botánico, Parque de los Deseos, Parque Explora and Parque Norte. Were developed studios like environmental measures, surveys like subjective test and audio recordings about the environmental sound. The research is developed in 3 key phases, with regular traffic, in the day without car and in the implementation of the environmental pico y placa (23rd, 24th and 25th of march 2017). Founding what the principal source of pollution of the environmental noise is the road traffic